Working Capital Efficiency, Inflation, and Firm Value: Evidence from Emerging Markets - Iswandi Sukartaatmadja; Muchamad Bachtiar; Edi Nurachmad; Dewi Sarifah Tullah; Hen Su (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Efficient financial management is fundamental to sustaining firm value, particularly through effective working capital management. In emerging markets, firm value is highly sensitive to macroeconomic volatility, including inflationary pressures that distort cash flow cycles, increase operating costs, and alter liquidity dynamics. Despite extensive research on working capital management, evidence on how inflation moderates the relationship between working capital efficiency and firm value remains limited, especially within the consumer non-cyclical sector.Purpose: This study investigates the effect of Days Sales Outstanding (DSO), Days Inventory Outstanding (DIO), and Days Payable Outstanding (DPO) on firm value, as well as the moderating role of inflation.Design/methodology/approach: This study employs a quantitative approach using panel data from consumer non-cyclical companies listed on the Indonesia Stock Exchange during 2015–2024. Firm-level financial data were obtained from audited annual reports, while inflation data were sourced from Bank Indonesia. The analysis uses a fixed-effects panel regression model estimated in Stata 17. Firm value is proxied by Tobin's Q, and control variables include firm size, profitability, leverage, and firm age.Findings/Result: DSO shows no significant effect before or after moderation (H1, H4 rejected), reflecting that receivable efficiency is not a market valuation driver in stable, demand-driven sectors. DIO significantly and negatively affects firm value (β = −0.003; p = 0.010), consistent with CCC theory, yet becomes insignificant under inflation (H5 rejected), suggesting that rising input costs prompt firms to adopt strategic inventory buffering rather than efficiency-driven reduction. DPO positively and significantly influences firm value (β = 0.010; p < 0.01), and inflation amplifies this effect (β = 0.428; p = 0.005; H6 supported), aligning with Signaling Theory, as extended payables under inflationary conditions signal financial resilience to investors.Conclusion: Inflation asymmetrically moderates the working capital firm value nexus strengthening DPO's positive effect while leaving DSO and DIO unaffected confirming that adaptive payables management is the dominant strategic lever for sustaining firm value under macroeconomic stress.Originality/value: This study provides new empirical evidence on how inflation interacts with working capital components to influence firm value, highlighting the relevance of macro-financial integration in corporate decision-making. Keywords:  working capital, inflation, firm value, operating costs, emerging markets